Immigrati: una sfida per la psichiatria - Carnevali, Rossella; Anzilotti, Carlo; Fiori Nastro, Paolo (Il sogno della farfalla, 2012)
Stemming from an experience had with immigrant psychiatric patients within the Françoise Minkowska Centre in Paris, specialized in the field of transcultural psychiatry and whose working method is here illustrated, the article questions, in general, the reactions that the immigrant patient evokes in the psychiatrist and the influence he exerts on the latter’s professional training. If we consider the fact that the current professional training of a psychiatrist does not offer an adequate preparation, the authors claim that the relationship with the foreign patient enriches the psychiatrist by forcing him to take a deeper and more complete look at the patient.